(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: This study aims to determine the positive response rate of healthcare staff on patient safety culture at Can Tho Obstetrics and Gynecology Hospital and analyze some related factors. Materials and methods: The cross-sectional study surveyed 313 healthcare staff who directly take care of patients (doctors, nurses, midwives, technicians) and have worked for at least 01 year at Can Tho Obstetrics and Gynecology Hospital during the research period, from October 2020 to June 2021. Result: In dimension 4, the positive response rate of management support was 98.56%. In dimension 2, the positive response rate of “supervisor/officer-in-charge actions promoting patient safety” was 98.08%. In dimension 1, the positive response rate of “teamwork within units” was 97.68%. In dimension 5, the positive response rate of “feedback and communication error” was 92.55%. In dimension 9, the positive response rate of “handoffs and transitions” was 88.39%. In dimension 3, the positive response rate of “supervisor/officer-in-charge expectations” was 86.58%. In dimension 8, the positive response rate of “teamwork across units” was 85.62%. In dimension 6, the positive response rate of “communication openness” was 82.32%. In dimension 10, the positive response rate of “non punitive response error” was 78.59%. In dimension 7, the positive response rate of “frequency of events reported” was 69.17%. Analyzing an association between professional titles and dimension-based satisfaction shows that “supervisor/officer-in-charge expectations” (Dimension 3) and “teamwork across units” (Dimension 8) of healthcare staff having different professional titles are different (p<0.05). Analyzing an association between main workplaces (units) and dimensionbased satisfaction shows that “management support” (Dimension 4) of healthcare staff in different unit is different (p<0.05). Conclusion: The positive response rate of healthcare staff on patient safety culture had a high range, from 69.17% to 98.56%. In 10 dimensions, the positive response rate of “frequency of events reported” was the lowest (69.17%), while that of “management support” was the highest (98.56%).